Techno-economic analysis of illegal electricity usage in Turkey and policy proposals - (:unkn) unknown (World Scientific and Engineering Academy and Society, 2010)
Some part of the energy produced in electric power systems does not reach to consumers who make payment because of output loss and administrative applications. The energy loss can be considered in two categories as technical losses and nontechnical losses. Total of these losses is a significant parameter that affects capacity of the system. In this study, the transmission and distribution losses in Turkey power system were researched. The studies carried out for purpose of determining its illegal use and its socio-economical effects were analyzed. It is impossible to prevent the losses completely in the electric energy system. However, in developed countries, it generally remains below 6%. The lost illegal use rate in Turkey was determined as 14.4%. The cost resulting from only illegal use reaches to values that urge the economy of Turkey with a rate that is 1.7 times of the annual transmission and distribution system investment of the country. In terms of energy pricing Turkey is very competitive situation with European Union and OECD countries. However, the losses of Turkey are well above the world and OECD averages. To decrease the technical losses, very serious additional energy investment is needed in the country. Illegal use rate can be decreased to acceptable rates as a result of policy changes and some measures. In the study, some solution suggestions are made to decrease the loss rate that occurs as a result of illegal use. To achieve decrease in illegal use, some measures can be taken such as, speeding up privatization policies, regional price policies, raising of the awareness of the public about economical and social dimensions of the illegal electric use, encouraging of the public to use other energy sources means by being informed and supported economically, awarding of the government officials who determine the illegal use, giving of various incentives to citizens who denounce such use.
Keywords: Cost; Electrical energy demand; Electricity theft; Energy generation; T&D loses